2012
DOI: 10.1055/s-0032-1320063
|View full text |Cite
|
Sign up to set email alerts
|

Nonsyndromic Craniosynostosis

Abstract: Nonsyndromic craniosynostosis is more commonly encountered than syndromic cases in pediatric craniofacial surgery. Affected children display characteristic phenotypes according to the suture or sutures involved. Restricted normal growth of the skull can lead to increased intracranial pressure and changes in brain morphology, which in turn may contribute to neurocognitive deficiency. Management has primarily focused on surgical correction of fused sutures prior to 12 months of age to optimize correction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
109
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 35 publications
0
109
0
Order By: Relevance
“…13 Although there are clear benefits to earlier surgical correction, surgery before 3 months of age is not recommended due to greater risk of blood loss. 5 Furthermore, infants who undergo surgical correction before 6 months of age may have higher rates of reoperation. 20 Thus, surgical intervention is generally recommended between 6 and 9 months.…”
Section: National Trends In Craniosynostosis Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…13 Although there are clear benefits to earlier surgical correction, surgery before 3 months of age is not recommended due to greater risk of blood loss. 5 Furthermore, infants who undergo surgical correction before 6 months of age may have higher rates of reoperation. 20 Thus, surgical intervention is generally recommended between 6 and 9 months.…”
Section: National Trends In Craniosynostosis Surgerymentioning
confidence: 99%
“…Unilateral coronal synostosis occurs slightly more commonly in females (3 to 2). 5 Whether the deformity leads to increased intracranial pressure, decreases in intracranial volume, and hydrocephalus is controversial. However, multiple studies have demonstrated an association of craniosynostosis with increased intracranial pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In presentscenario developing of the molecular biology a new and very innovative consepts are coming to controlling these disease. The etiopathogenesis, neurocognitive impairment stated and we specifically observed in our day today experience in these diseases these infants are suffering in mutations (point, substitutional, deletion, addition, allelespecific, missense and haplotypes) [1].…”
Section: Introductionmentioning
confidence: 87%
“…An idea germinating in these concepts in experimental observations to overcome this globally burden. We are trying to develop and targeting genetic therapy to prevent pathologically sutural fusion and at the same time other defects by birth [1]. TNFRSF11B plus Vitamin-D Deficiency in infancy was associating with severs JPD [2] which complicated by craniosynostosis.…”
Section: Introductionmentioning
confidence: 99%